Some problems of the ecological assessment of real estate - Marinova, Tsvetelina; Mardirossian , Garo (Annual of Natural Sciences Department, 2022)
Real estate investment is widely regarded as one of the most reliable and lucrative forms of investment. Unfortunately, properties are offered and purchased without even the most basic data of their ecological and geophysical characteristics – not only in Bulgaria, but also globally. This study presents a pioneer attempt to identify the various issues concerning the environmental valuation of real estate. The study outlines the components, objects, as well as methods and technical instruments for such evaluation.